Metacognition, mindfulness and cross-cultural adjustment - Cao, Ying (2008)
This study examines the relationship of expatriates’ Cultural Intelligence (CQ) and Mindfulness with their cross-cultural adjustments (work, interaction and general adjustment). In particular, the Metacognition facet of CQ was integrated with Mindfulness to explore their collective power in predicting cross-cultural adjustment. Correlation and regression analyses were conducted to test these hypotheses. Results based on data of 136 expatriates and 116 significant others demonstrated significant positive relationships between Metacognition with work and interaction adjustment after controlling for age, gender and work experience abroad, while ecentering facet under Mindfulness (Mindfulness-decentering) significantly related to all three aspects of adjustment under the same regression analyses. Further analyses on significant other assessments of expatriates were conducted to seek additional support for our hypotheses. This paper concludes by providing practical implications for organizations and suggestions for future research.